Corrida cinco estrelas: voz dos motoristas de aplicativos sobre seu trabalho na cidade de São Paulo - Barbosa, Daniel Casseb (2021)
At times when society is in a transition of models the way we work, the question is: and where will people go? In this academic research, we sought to describe, after hearing UBER drivers in the city of São Paulo, what were their motivations, how they work, to understand what their work context is and what conditions they are subjected to behind the wheel. It also points to the search for clarity regarding the consolidation of the informal labor market, driven by the current financial crisis. The opportunities for informal work, the precariousness arising and finally the gig economy. In addition, a critical look at the new phenomenon called uberization. All these elements make up the research for this work.